Computed tomographic findings of brain and skull in myotonic dystrophy. Issue 4 (April 1987) - Avrahami, E; Katz, A; Bornstein, N; Korczyn, A D
Abstract : Twenty-four patients with myotonic dystrophy underwent computed tomographic examination of the skull and brain. The results were compared with those of 20 normal subjects of similar age and sex distribution. Microcephaly and thickening of the calvarium were frequently observed. Some cases showed basal ganglia calcification. Our findings confirm that cranial hyperostosis and brain pathology is a common manifestation of this systemic disease.